Nuclear recoil correction to the g factor of boron-like argon. (29th January 2015) - Shchepetnov, A A; Glazov, D A; Volotka, A V; Shabaev, V M; Tupitsyn, I I; Plunien, G
Abstract: The nuclear recoil effect to the g factor of boron-like ions is investigated. The one-photon-exchange correction to the nuclear recoil effect is calculated in the nonrelativistic approximation for the nuclear recoil operator and in the Breit approximation for the interelectronic-interaction operator. The screening potential is employed to estimate the higher-order contributions. The updated g -factor values are presented for the ground 2 P 1/2 and first excited 2 P 3/2 states of B-like argon 40 Ar 13+, which are presently being measured by the ARTEMIS group at GSI.